The Ukhuwah Paradigm in The Regulation on Majelis Taklim in Indonesia - Naswa Aliyah Prerianda; Rahmila Nurul Izzani Fajri; Najwa Azzahra Karimah; In’am Salsabila; Kholifatunnisa’ Kholifatunnisa’; Ratih Khikmah Hidayah (TATHO: International Journal of Islamic Thought and Sciences, 2024)
The purpose of this study is to identify the values of Islamic solidarity formation in the Minister of Religious Affairs Regulation No. 29 of 2019 concerning Majelis Taklim. This qualitative research uses a literature study with a normative-philosophical approach.  The trilogy of ukhuwah becomes the theory of analysis of the main object of research. Data for research was obtained using documentary techniques. While data analysis is carried out with the stages of reduction, presentation and verification. This research found the dimensions of the trilogy of ukhuwah values in regulations related to the orientation of majelis taklim in Indonesia, including the value of ukhuwah Islamiyah in increasing religiosity. Then, the value of ukhuwah wathoniyah in maintaining the integrity of social and cultural life. Furthermore, the value of ukhuwah basyariah in building a pluralist and humanist life. The results of this study confirm that the value of the trilogy of ukhuwah in Indonesia can be internalised through the orientation of the implementation of Islamic education, both formal and informal. The limitations of this research have not reviewed the role of Majelis Taklim in the community in internalising the trilogy of ukhuwah.